(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Photocatalytic degradation of a model compound of the carbamate insecticide carbofuran in water was studied using polychromatic light and ZnO and TiO2 catalysts. The influence of operational parameters, such as reaction time and initial carbofuran concentration, on photocatalytic degradation was studied. A pseudo-first-order kinetic model was established and an almost complete removal of 88.4 mg L–1 of carbofuran occurred within 2 h under optimized conditions. The reactions were examined by UV spectroscopy and high performance liquid chromatography (HPLC). In addition, the photocatalytic efficiencies of ZnO and TiO2 were compared under the same reaction conditions.